How Transparency Kills Information Aggregation: Theory and Experiment - Sebastian Fehrler; Niall Hughes (Institute for the Study of Labor (IZA), 2015)
We investigate the potential of transparency to influence committee decision-making. We present a model in which career concerned committee members receive private information of different type-dependent accuracy, deliberate and vote. We study three levels of transparency under which career concerns are predicted to affect behavior differently, and test the model's key predictions in a laboratory experiment. The model's predictions are largely borne out - transparency negatively affects information aggregation at the deliberation and voting stages, leading to sharply different committee error rates than under secrecy. This occurs despite subjects revealing more information under transparency than theory predicts.
Keywords: C92; D71; D83; 330; committee decision-making; deliberation; transparency; career concerns; information aggregation; experiments; voting; strategic communication